2020
DOI: 10.3390/molecules26010051
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds of Lemon and Grapefruit IntegroPectin

Abstract: An HS-SPME GC-MS analysis of the volatile compounds adsorbed at the outer surface of lemon and grapefruit pectins obtained via the hydrodynamic cavitation of industrial waste streams of lemon and grapefruit peels in water suggests important new findings en route to understanding the powerful and broad biological activity of these new pectic materials. In agreement with the ultralow degree of esterification of these pectins, the high amount of highly bioactive α-terpineol and terpinen-4-ol points to limonene (a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…On the other hand, little or no protection was exerted by commercial citrus pectin indicating that only lemon IntegroPectin exerts a protective role on the cell's central organelle, involved in several pathological dysfunctions. We ascribe these findings to the combined action of the terpenes [40] and flavonoids [59] adsorbed at the surface of the pectic polymer as well as to the unique structure of this new pectin of low degree of esterification and with a more pronounced abundance of RG-I "hairy" regions rich in galactose and arabinose units, capable to bind and inhibit β-galactoside-binding lectin galectin-3. As recently remarked by Sobarzo-Sánchez and co-workers suggesting the need for further clinical trials, a few clinical studies have already shown that hesperidin-enriched dietary supplements can significantly improve cerebral blood flow, cognition, and memory performance [46].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, little or no protection was exerted by commercial citrus pectin indicating that only lemon IntegroPectin exerts a protective role on the cell's central organelle, involved in several pathological dysfunctions. We ascribe these findings to the combined action of the terpenes [40] and flavonoids [59] adsorbed at the surface of the pectic polymer as well as to the unique structure of this new pectin of low degree of esterification and with a more pronounced abundance of RG-I "hairy" regions rich in galactose and arabinose units, capable to bind and inhibit β-galactoside-binding lectin galectin-3. As recently remarked by Sobarzo-Sánchez and co-workers suggesting the need for further clinical trials, a few clinical studies have already shown that hesperidin-enriched dietary supplements can significantly improve cerebral blood flow, cognition, and memory performance [46].…”
Section: Discussionmentioning
confidence: 93%
“…In previous works, we have shown the advantages of hydrocavitation for improving the biological activity of citrus pectin [22,24]. The essential oils (EOs) emulsify in water during the hydrocavitation of citrus processing waste (CPW), with limonene (the main citrus EO component) and linalool being converted into highly bioactive α-terpineol and terpinen-4-ol due to acid catalysis promoted by citric acid residual in the CPW enhanced by the implosion of the cavitation bubbles [40]. Freeze-dried pectin obtained along with flavonoids and said emulsified citrus oil upon lyophilization contains the integral water-soluble part of waste citrus peel, including the flavonoids in a highly concentrated fashion, and constitutes a completely new biomaterial, accordingly named "IntegroPectin" [22][23][24]40,41].…”
Section: Structural Insightmentioning
confidence: 99%
“…It is likely that its dispersion on the highly soluble fibers of grapefruit IntegroPectin obtained upon freeze drying enhances its bioavailability. Grapefruit IntegroPectin, furthermore, is rich in adsorbed limonene, linalool and linalool oxide (predominantly the cis isomer) [21].…”
Section: Figure 6 X-ray Diffractograms Of Grapefruit Integropectin (A) and Commercial Citrus Pectin (B)mentioning
confidence: 99%
“…Among the latter, hydrodynamic cavitation has been lately first applied to waste orange peel [18] as well as to lemon and grapefruit [19] biowaste resulting from Citrus fruit juice extraction. Rich in flavonoids [20] and terpenes [21], the IntegroPectin resulting from freeze-drying of the aqueous hydrocavitated extract has exceptionally high antioxidant activity and lacks cytotoxicity even at high concentration [19]. Furthermore, lemon and grapefruit IntegroPectin show significant antibacterial activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of essential oils is usually energy-consuming and not environmentally friendly, as the most common methods include steam distillation and solvent extraction. Lately, hydrodynamic cavitation has been successfully applied to the green, effective and efficient extraction of bioactive compounds, proteins, polysaccharides, flavors, fragrances, essential oils and fine chemicals (pigments and dyes) from plant materials [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%